Relationship between post-stroke spasticity and functional ambulation among Nigerian stroke survivors (2021)
Ambulation is a common goal of stroke rehabilitation that is often linked to lower limb spasticity. This study was conducted to investigate the relationship between paretic lower limb spasticity and functional ambulation after stroke. Thirty stroke survivors (19 males) aged 57.77 ± 9.52 years participated in this correlational cross-sectional study. Spasticity of the paretic lower limb was assessed using the Modified Tardieu Scale. Functional ambulation performance was assessed using the Emory Functional Ambulation Profile (E-FAP). Data were analyzed using Pearson's product moment correlation and stepwise regression analysis at p = 0.05. Spasticity was highest in the ankle plantaflexors (253.20 ± 32.62°). There was a significant relationship between spasticity of the affected lower limb and functional ambulation performance (r=0.61; p<0.05) Stepwise regression analysis indicated that only spasticity of the ankle plantaflexors predicted functional ambulation. Spasticity of the paretic ankle plantaflexors has discriminative power for predicting functional ambulation. This underscores the need for focused rehabilitation aimed at reducing spasticity of ankle plantaflexors for improved functional ambulation among stroke survivors.